hsCRP in pre-hypertension and hypertension: a prospective study in Southern Asian region - Sinha, Satwika; Kar, Kaushik; Soren, Monoj; Dasgupta, Anindya (International Journal of Research in Medical Sciences, 2017)
Background:Hypertension is turned into a leading cause of non-communicable disease associated mortality and morbidity in both developing as well as developed world. Hypertension is reported to be the fourth contributor to premature death in developed countries and the seventh in developing countries. In the regard of early diagnosis and better prognosis, the concept of pre-hypertension, defined as a systolic blood pressure of 120-139 mmHg and/or a diastolic blood pressure of 80-89 mmHg was introduced as the new guideline for the management of blood pressure by the seventh report of the Joint National Committee on prevention, detection, evaluation, and treatment of high blood pressure (JNC-7). Among various other factors inflammation may be a causative factor for development of Hypertension But the association is not very clear. Accordingly, we have designed our study to find any association of hsCRP with pre-hypertension and hypertension so that early prevention and control can help to avoid or delay the grave outcome and complications of hypertension. Methods:A total of 37 hypertensives, 30 pre-hypertensives and 31 age and sex matched healthy control subjects were selected for the study, with consent. Two BP readings were taken five minutes apart, on both arms, with a mercury sphygmomanometer. The estimation of serum hsCRP was done on XL-600 automatic analyzer with the kit (Erba Mannheim) based on the measurement of antigen-antibody reaction by the end-point method. Results:There is significant difference in systemic and diastolic blood pressure and hsCRP in between group study. In pre-hypertensive group hsCRP is correlated with diastolic blood pressure. Conclusion:Our results suggest a correlation exists between hsCRP and hypertension more significantly with pre-hypertension. So estimation of serum hsCRP can be a good diagnostic as well as prognostic marker in diagnosing pre-hypertensives and prevent the occurance of hypertension and cardio vascular disorders thereby.